2011
DOI: 10.1095/biolreprod.111.092304
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Human Oxytocin Receptor Promoter by CCAAT/ Enhancer-Binding Protein and RELA1

Abstract: Uterine activation is associated with increased oxytocin receptor (OXTR) expression and myometrial sensitivity to oxytocin. The OXTR promoter contains binding sites for CCAAT/enhancer-binding protein (CEBP) and nuclear factor-kappa B p65 (RELA). RELA and CEBP beta (CEBPB) play a synergistic role in OXTR promoter activation. We created deletions in a DNA construct consisting of 850 bp upstream of the transcription start site linked to luc reporter to identify the CIS element of the OXTR promoter responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Taken together, it would let us suggest that PGF2A stimulates PTGS2 through different signalling pathways in different types of cells. Some studies have demonstrated that NFkB activation induces OTR expression in myometrium (Khanjani et al 2011). Herein, we found that NFkB was not involved in PGF2A stimulation of OTR in myometrial cells.…”
Section: Discussionmentioning
confidence: 50%
“…Taken together, it would let us suggest that PGF2A stimulates PTGS2 through different signalling pathways in different types of cells. Some studies have demonstrated that NFkB activation induces OTR expression in myometrium (Khanjani et al 2011). Herein, we found that NFkB was not involved in PGF2A stimulation of OTR in myometrial cells.…”
Section: Discussionmentioning
confidence: 50%
“…Khanjani et al. propose that oxytocin receptor gene regulation depends on the synergistic cooperation of NF κ B and CEBP, and that the cooperation and binding of both transcription factors to the OXTR gene is increased by IL‐1 β , the expression of which is also regulated by NF κ B …”
Section: Nfκb and Labourmentioning
confidence: 99%
“…85 Khanjani et al propose that oxytocin receptor gene regulation depends on the synergistic cooperation of NFjB and CEBP, and that the cooperation and binding of both transcription factors to the OXTR gene is increased by IL-1b, the expression of which is also regulated by NFjB. 86 To summarise, NFjB has been implicated in numerous processes related to human labour. Literature data indicate that an elevated NFjB level at term is linked with the following processes: (1) activation of metalloproteinases, implicated in the degradation of fetal membranes as well as in the preparation of the reproductive system for an influx of inflammatory cells; (2) regulation of the inflammatory response, which allows the stimulation of COX-2 and prostaglandins; (3) control of COX-2 gene expression; and (4) regulation of gene expression of contraction-associated protein and the oxytocin receptor.…”
Section: Nfjb and Labourmentioning
confidence: 99%
“…But, regulation of OXTR gene function by P in pregnant myometrium is most likely indirect via immunosuppressive actions of P [as reviewed by Arck et al (2007)]. Recently, binding sites for nuclear factor-kappa B p65 (RELA) and CCAAT/enhancer-binding protein (CEBP) were identified in the human OXTR gene promotor region (Khanjani et al, 2011). Expression of CEBP and RELA are increased in inflammatory responses (Adams et al, 2000), and mediators of both are increased in near-term myometrium of women (Khanjani et al, 2011).…”
Section: Effects Of Progesterone On Oxtr Gene Expressionmentioning
confidence: 99%